Emerging technologies in computing : second International Conference, iCETiC 2019, London, UK, August 19-20, 2019 : proceedings /: second International Conference, iCETiC 2019, London, UK, August 19-20, 2019 : proceedings. ([2019]) - Unknown
No abstract available